2014
DOI: 10.1158/0008-5472.can-13-2259
|View full text |Cite
|
Sign up to set email alerts
|

Local and Systemic Protumorigenic Effects of Cancer-Associated Fibroblast-Derived GDF15

Abstract: The tumor stroma is vital to tumor development, progression, and metastasis. Cancer-associated fibroblasts (CAF) are among the abundant cell types in the tumor stroma, but the range of their contributions to cancer pathogenicity has yet to be fully understood. Here, we report a critical role for upregulation of the TGFb/BMP family member GDF15 (MIC-1) in tumor stroma. GDF15 was found upregulated in situ and in primary cultures of CAF from prostate cancer. Ectopic expression of GDF15 in fibroblasts produced pro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 44 publications
2
83
0
Order By: Relevance
“…In the present study too, the GDF15-positive cells in the ESCC tissues were mostly confined to the cytoplasm of ESCC cells, whereas GDF15 immunoreactions were detected in other stromal cells such as erythrocytes and macrophages. Although GDF15 expression has been reported in bone marrow stromal cells in multiple myeloma and cancer-associated fibroblasts in prostate cancer, 45,46 this may be the first report of GDF15 expression in TAMs. The serum GDF15 concentration has been reported to be closely associated with the depth of invasion, lymph node metastasis, and overall survival of ESCC patients.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 76%
“…In the present study too, the GDF15-positive cells in the ESCC tissues were mostly confined to the cytoplasm of ESCC cells, whereas GDF15 immunoreactions were detected in other stromal cells such as erythrocytes and macrophages. Although GDF15 expression has been reported in bone marrow stromal cells in multiple myeloma and cancer-associated fibroblasts in prostate cancer, 45,46 this may be the first report of GDF15 expression in TAMs. The serum GDF15 concentration has been reported to be closely associated with the depth of invasion, lymph node metastasis, and overall survival of ESCC patients.…”
Section: Gdf15 Increased the Growth Of The Escc Cell Lines By Triggermentioning
confidence: 76%
“…The following reasons could possibly be responsible for the close association between increased tumor-infiltrating podoplanin + fibroblasts and worse outcome of patients presented in this study: Fibroblasts in the TME are able to promote tumor cell invasion, proliferation and survival through releasing growth factors, cytokines [39] and extracellular matrix-degrading proteases such as matrix metalloproteinases (MMPs) (e.g. MMP1) [40].…”
Section: Discussionmentioning
confidence: 97%
“…Many studies also consider that GDF15 is a contributor to the development and progression of some malignant tumors [20, 21, 3638], although several documents have reported that retinoid-related molecule or anti-inflammatory drug can induce tumor cell apoptosis via GDF15 [3941]. Bruzzese F 20 points out that the pro- and anti-tumor activities of GDF15 are highly dependent on the cellular and microenvironmental context.…”
Section: Discussionmentioning
confidence: 99%